A Criterion for Flow‐Induced Oriented Crystals in Isotactic Polypropylene under Pressure. Issue 23 (28th September 2017) - Yang, Shu‐Gui; Ma, Zhe; Lei, Jun; Li, Liangbin; Hsiao, Benjamin S.; Li, Zhong‐Ming
Abstract: Flow‐induced oriented crystals have attracted considerable attention because they significantly increase stiffness and strength of polymer products. Naturally, understanding the necessary condition of forming oriented crystals is of importance for both industry and polymer physics. Following the concept of specific work of flow proposed by Mykhaylyk and co‐workers, the expression of the specific work of flow, w (T, P), was carefully summarized and verified that when w (T, P) is above a critical specific work of flow, w c(T, P) = (1.7 ± 0.7) × 10 7 J m −3, oriented crystals in isotactic polypropylene can be induced by flow at pressures (50, 100, and 150 MPa) and at a undercooling of 65 K. The influences of pressure on w c(T, P) stem from two facets: one is the influence on the melt viscosity (the Barus law), and the other one is the influence on the equilibrium melting temperature (the Clapeyron equation). The current study can guide real processing to fabricate high‐performance polymer products with oriented crystals. Abstract : Flow‐induced oriented crystals in isotactic polypropylene (iPP) crystallized under pressure are successfully described by the modified specific work of flow, w (T, P) . When w (T, P) is above the critical specific work of flow, w c(T, P) = (1.7 ± 0.7) × 10 7 J m −3, oriented crystals in iPP can be induced by flow at pressures (50, 100, and 150 MPa) and at an undercooling of 65 K.